Preservation of biomacromolecular composition and ultrastructure of a decellularized cornea using a perfusion bioreactor. Issue 3 (4th January 2016) - Nara, Sharda; Chameettachal, Shibu; Midha, Swati; Murab, Sumit; Ghosh, Sourabh
Abstract : An attempt has been made to formulate a new method of corneal decellularization using a direct perfusion through the cornea to preserve matrix ultrastructure. Abstract : An attempt has been made to formulate a new method of corneal decellularization using a direct perfusion system through the cornea. Here, we compared the direct perfusion method to some commonly used decellularization strategies including chemical methods; non-ionic detergent TRITON X-100 and ionic detergent; sodium dodecyl sulphate (SDS) based orbital shaker method and physical methods of liquid nitrogen and freeze–thaw to decellularize a goat cornea. Histochemical evaluation and biochemical estimation highlighted that liquid nitrogen, freeze–thaw and TRITON-based orbital shaker methods resulted in incomplete removal of resident cells from the native cornea. On the contrary, direct perfusion of the cornea using TRITON and SDS completely removed all the cells from the cornea while preserving the ultrastructure of the extracellular matrix at a steady flow rate of 10 μl min −1 . Raman and ATR-FTIR spectra indicated the relative abundance of the α-helical conformation of collagen type I in the perfused cornea while a β-sheet conformation was predominantly observed in other treatment methods. FACS was used to determine the cell death modality in different methods of decellularization. In the direct perfusion system, 13.1% higher apoptotic cells, the preferred route of cell death, were observed in the cornea compared to orbital shaker-based methods. Further, feasibility studies conducted for 7 days to investigate the recellularization potential of the perfused decellularized matrix demonstrated a well attached viable population of seeded corneal stromal cells. In summary, we demonstrated that the direct perfusion method for decellularization of a cornea using 0.1% TRITON detergent at 10 μl min −1 is an optimal strategy for efficiently removing the resident corneal cells while maintaining the ultrastructure of the corneal matrix intact and therefore could serve as an excellent source for corneal transplantation.